2021
DOI: 10.3390/jpm11020105
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Characterizing of CD24 Knockout Mouse—Cognitive and Emotional Alternations

Abstract: CD24 is a small, glycophosphatidylinositol-anchored cell surface protein, mostly investigated with respect to cancer, inflammation, and autoimmune diseases. CD24 knockdown or inhibition has been used to test various biochemical mechanisms and neurological conditions; however, the association between CD24 and behavioral phenotypes has not yet been examined. This study aims to characterize cognitive and emotional functions of CD24 knockout mice (CD24−/−) compared with CD24 wild-type mice at three time-points: ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…It was found that the level of CD24hi cells was correlated with the occurrence of myocardial infarction (38). Meanwhile, animal experiments showed that CD24 gene knockout improved anxiety-like behavior and cognitive performance in mice (39). In our study, the expression level of CD24 was also found to be increased in blood samples of patients with depression, suggesting that CD24 may be potentially related to emotional regulation.…”
Section: Discussionsupporting
confidence: 57%
“…It was found that the level of CD24hi cells was correlated with the occurrence of myocardial infarction (38). Meanwhile, animal experiments showed that CD24 gene knockout improved anxiety-like behavior and cognitive performance in mice (39). In our study, the expression level of CD24 was also found to be increased in blood samples of patients with depression, suggesting that CD24 may be potentially related to emotional regulation.…”
Section: Discussionsupporting
confidence: 57%